Lava Dome Morphology and Viscosity Inferred From Data-Driven Numerical Modeling of Dome Growth at Volcán de Colima, Mexico During 2007-2009 - Zeinalova, Natalya; Ismail-Zadeh, Alik; Melnik, Oleg; Tsepelev, Igor; Zobin, Vyacheslav (Frontiers in Earth Science, 2021)
Magma extrusion, lava dome growth, collapse of domes, and associated pyroclastic flow hazards are among important volcanological studies. In this paper, we analyze the influence of the magma viscosity and discharge rates on the lava dome morphology at Volcán de Colima in Mexico during a long dome-building episode lasting from early 2007 to fall 2009 without explosive dome destruction. Camera images of the lava dome growth together with recorded volumes of the erupted lava have been used to constrain numerical modeling and hence to match the history of the dome growth by nudging model forecasts to observations. Our viscosity model incorporates crystal growth kinetics and depends on the characteristic time of crystal content growth (or CCGT) and the crystal-free magma viscosity. Initially, we analyze how this viscosity, CCGT, and the rate of lava extrusion influence the morphology of the growing dome. Several model scenarios of lava dome growth are then considered depending on the crater geometry, the conduit location, the effective viscosity of dome carapace, and the extrusion rates. These rates are determined either empirically by optimizing the fit between the morphological shape of modeled domes and that of the observed dome or from the recorded lava dome volumes. The maximum height of the modeled lava dome and its horizontal extent are in a good agreement with observations in the case of the empirically-derived extrusion rates. It is shown that the topography of the crater at Volcán de Colima is likely to be inclined toward the west. The viscosity of the modeled lava dome (∼1012 Pa s) is in a good agreement with the effective viscosity estimated experimentally from lavas of Volcán de Colima. Due to the interplay between the lava extrusion and the gravity forces, the dome reaches a height threshold, and after that a horizontal gravity spreading starts to play an essential role in the lava dome evolution. The model forecasts that the dome carapace of higher viscosity (∼1014 Pa s) influences the dome growth and its morphology during long dome-building episodes by retarding horizontal advancement and developing steep-sided eastern edge of the dome at the volcano. The developed model can be used in assessments of future effusive eruptions and lava dome growth at Volcán de Colima or elsewhere. History matching modeling of lava dome growth sheds a light on dynamic processes inside the dome and may assist in assessing stress state in the dome carapace and in forecasting the dome failures.